Emergency department staff knowledge of massive transfusion for trauma: the need for an evidence based protocol. Issue 10 (28th October 2010) - Milligan, C; Higginson, I; Smith, J E
Abstract : Introduction: Uncontrolled haemorrhage is the leading cause of potentially reversible early in-hospital death following trauma. Approximately 25% of trauma patients arriving in the emergency department have evidence of early coagulopathy. It is vital that staff within the emergency department understand the basic pathophysiological consequences of massive blood loss in trauma and are familiar with when and how to administer blood and specific blood components in trauma resuscitation. Methods: A structured questionnaire designed to test knowledge of the use of blood and blood components in trauma resuscitation was distributed to the emergency physicians attending a regional conference in the South West of England. The questionnaire consisted of 16 questions, both multiple choice and short answer format, referenced via Medline. Results: 32/32 questionnaires distributed were completed and returned. Massive transfusion protocols existed in 4/11 hospitals surveyed. 5/32 doctors were able to define the term 'massive transfusion' while 9/32, 6/32 and 3/32 were consistent with current guidelines in their prescription of platelets, fresh frozen plasma, and cryoprecipitate. 20/32 were consistent with current guidelines in identifying optimal haemoglobin levels. When asked more specifically about blood component therapy, 18/32 correctly identified target fibrinogen levels, 27/32 knew that fibrinogen is a component of fresh frozen plasma or cryoprecipitate and 1/32 correctly identified that fibrinogen is a component of both. 10/32 identified indications for beriplex and 5/32 doctors correctly identified indications for the use of recombinant factor VIIa. 20/32 doctors guessed >50% of the answers and the remaining 12/32 guessed 50%. Conclusions: The survey found that emergency physicians lacked core knowledge about the use of blood and blood component therapy in the context of massive haemorrhage following trauma. Doctors were unaware of how to prevent and treat early coagulopathy. Educational resources specifically for use by emergency physicians are limited on this topic. The use of massive transfusion protocols—that standardised blood component therapy is automatically delivered at specific points within resuscitation—would not only guide doctors, but be a clear step towards minimising the complications associated with massive transfusion.